BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2002)
Topics in Tropical Virology. Vol.l. Editors: Donald N. Black, Dharma D. Shukla and Narayan Rishi, Malhotra Publishing House, New Delhi, 1998, 180 pp. Disease of Horticultural crops -Fruits. Editors: L.R. Verma and R.c. Sharma. Indus 'Publishing Company, New Delhi, 724 pp. Rs. 1200. Pathological Problems of Economic Crop Plants and their Management. Editor : S.M. Paul Khurana, 1998,665 pp, 24 cm X 16cm (ISBN: 81 -7233 -178 -9), Scientific Publisher (India), Jodhpur 342 001, PB # 91.